2010
DOI: 10.1088/1757-899x/8/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

The influence of annealing temperature on ReRAM characteristics of metal/NiO/metal structure

Abstract: The resistive switching of NiO sandwiched between Pt bottom and top electrodes are formed by thermal oxidation at the temperature from 300°C to 800°C. The ReRAM characteristics are investigated from the view point of practical applications. The stable and uniform formation of NiO films are revealed by XPS analysis and the chemical compositions of NiO are almost independent of oxidation temperatures. However, the forming voltages of the film prepared at higher oxidation temperature are scattered and reach to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
4
10
0
Order By: Relevance
“…The I-V curve in Fig. 5 is quite similar to that of the data during the forming process for Pt/NiO/Pt devices measured in air, 7 while the switching voltage and current are slightly different. Therefore, the bridge observed in this work is thought to be a conductive filament used in the operation of ReRAMs.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The I-V curve in Fig. 5 is quite similar to that of the data during the forming process for Pt/NiO/Pt devices measured in air, 7 while the switching voltage and current are slightly different. Therefore, the bridge observed in this work is thought to be a conductive filament used in the operation of ReRAMs.…”
Section: Resultssupporting
confidence: 68%
“…7 Therefore, commercially available Pt-Ir tips for scanning tunneling microscopy (STM) were used as electrodes in this work. One of the electrode tips was covered with a NiO layer and was used as the specimen we investigated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This oxidization condition may provide sufficient resistance switching properties as proved in Pt/NiO/Pt patterned devices (100-nm-thick and oxidized at 500-800 C) on SiO 2 /Si wafers. 16,24 The in-situ TEM observation system was composed of a custom-made TEM holder attached with a piezo actuator. [26][27][28][29] The TEM instrument we used was mainly a JEM-2010 microscope (200 kV, C s ¼ 0.5 mm, 10 À5 Pa) with a CCD video camera to record the TEM images.…”
Section: Methodsmentioning
confidence: 99%
“…The resistance switching of binary oxides such as NiO is mainly of the unipolar type that does not depend on the voltage polarity. [10][11][12][13][14][15][16] Recent works reported that the "filamentredox-model" (in short, the "filament model") is influential in unipolar resistance switching. 4,[17][18][19][20][21] In the first process of this ReRAM operation, a relatively high voltage applied to the initial ReRAM film in the high resistance state (HRS, off-state) changes it to the low resistance state (LRS, onstate).…”
Section: Introductionmentioning
confidence: 99%